Atmospheric pressure plasma jets onto a reactive water layer over tissue: pulse repetition rate as a control mechanism. (24th October 2018) - Norberg, Seth A; Parsey, Guy M; Lietz, Amanda M; Johnsen, Eric; Kushner, Mark J
Abstract: The use of plasma jets to treat tissue in the context of plasma medicine often involves a thin intervening liquid layer on top of the tissue. Plasma activated species first transport through and react in the liquid layer prior to reaching the tissue. Of the many parameters that can be used to control this process, pulse repetition frequency (PRF) stands out. Results from a computational investigation of multiple pulses at varying PRF from an atmospheric pressure plasma jet (APPJ) onto a reactive liquid layer are discussed, and three key trends are made clear. First, a high PRF (short time between pulses) enables the gaseous species produced during the previous pulse to remain in the vicinity of the plasma at the onset of the next pulse, thereby increasing the inventory of (H)N x O y and O3 in the gas phase. These species then solvate into the liquid, water in this case, and produce higher densities of aqueous ozone, nitrate, and peroxynitrite. With a lower PRF, reactants produced on a previous pulse are convected away prior to the next discharge pulse with more spatial separation of reactants both above and within the water. As a result, more of the hydroxyl anion ( ), ozone anion ( ) and nitric oxide (NOaq ) reach the tissue beneath the water. The second trend is that the production of H2 O2aq and its fluence to the underlying tissue are relatively independent of the PRF. The precursors for H2 O2aq are primarily produced by the surface ionization wave (SIW) on the top of the liquid, which then directly solvate into the liquid. Lastly, when the plasma plume touches the liquid, the SIW on the water layer increases the production of all aqueous species compared to configurations where the plasma plume does not touch the liquid. These trends are true for all PRF.